Iron-porphyrin encapsulated in poly(methacrylic acid) and mesoporous Al-MCM-41 as catalysts in the oxidation of benzene to phenol - Nur, Hadi; Hamid, Helda; Endud, Salasiah; Hamdan, Halimaton; Ramli, Zainab (Elsevier, 2006)
Poly(methacrylic acid) (PMAA) and mesoporous molecular sieve Al-MCM-41 with Si/Al = 20 were used as supports for the encapsulation of bulky iron(III)-5,10,15,20-tetra-(4-pyridyl)porphyrin (Fe-TPyP). Metalloporphyrin of Fe(III) was encapsulated inside the mesopores of Al- MCM-41 by a process of sequential synthesis of Fe-TPyP by treatment of FeCl3 with 5,10,15,20-tetra-(4-pyridyl) porphyrin (TPyP), followed by encapsulation of Fe-TPyP. Fe-TPyP complexes were also successfully encapsulated in PMAA by polymerizing a monomer (MAA) with a cross-linker around the Fe-TPyP complexes. The materials obtained were identified using XRD, UV–vis DR, FTIR and luminescence spectroscopies. The oxidation of benzene to phenol using aqueous hydrogen peroxide has been studied using both iron-porphyrin encapsulated in poly(methacrylic acid) and mesoporous Al-MCM-41 as catalysts. The encapsulated iron-porphyrin in PMAA (Fe-TPyP–PMAA) give a higher catalytic activity compared to Fe-TPyP encapsulated in Al-MCM-41 (Fe-TPyP–MCM-41). However, the product selectivity and the regenerability of Fe-TPyP–PMAA are not as good as than those of Fe-TPyP–MCM-41. One considers that the hydrophobic nature of Fe- TPyP–PMAA may account for the high catalytic activity, and the ordered structure of Fe-TPyP–MCM-41 may contribute to a high selectivity. © 2005 Elsevier B.V. All rights reserved.